Identification of a member of the interferon regulatory factor family that binds to the interferon-stimulated response element and activates expression of interferon-induced genes. - Au, W C (1995)
A family of interferon (IFN) regulatory factors (IRFs) have been shown to play a role in transcription of IFN genes as well as IFN-stimulated genes. We report the identification of a member of the IRF family which we have named IRF-3. The IRF-3 gene is present in a single copy in human genomic DNA. It is expressed constitutively in a variety of tissues and no increase in the relative steady-state levels of IRF-3 mRNA was observed in virus-infected or IFN-treated cells. The IRF-3 gene encodes a 50-kDa protein that binds specifically to the IFN-stimulated response element (ISRE) but not to the IRF-1 binding site PRD-I. Overexpression of IRF-3 stimulates expression of the IFN-stimulated gene 15 (ISG15) promoter, an ISRE-containing promoter. The murine IFNA4 promoter, which can be induced by IRF-1 or viral infection, is not induced by IRF-3. Expression of IRF-3 as a Gal4 fusion protein does not activate expression of a chloramphenicol acetyltransferase reporter gene containing repeats of the Gal4 binding sites, indicating that this protein does not contain the transcription transactivation domain. The high amino acid homology between IRF-3 and ISG factor 3 gamma polypeptide (ISGF3 gamma) and their similar binding properties indicate that, like ISGF3 gamma, IRF-3 may activate transcription by complex formation with other transcriptional factors, possibly members of the Stat family. Identification of this ISRE-binding protein may help us to understand the specificity in the various Stat pathways.